2017
DOI: 10.1371/journal.ppat.1006120
|View full text |Cite|
|
Sign up to set email alerts
|

HTLV-1 bZIP Factor Enhances T-Cell Proliferation by Impeding the Suppressive Signaling of Co-inhibitory Receptors

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) causes adult T-cell leukemia-lymphoma (ATL) and inflammatory diseases. To enhance cell-to-cell transmission of HTLV-1, the virus increases the number of infected cells in vivo. HTLV-1 bZIP factor (HBZ) is constitutively expressed in HTLV-1 infected cells and ATL cells and promotes T-cell proliferation. However, the detailed mechanism by which it does so remains unknown. Here, we show that HBZ enhances the proliferation of expressing T cells after stimulation via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 62 publications
4
48
1
Order By: Relevance
“…2 B ). This finding is compatible with the previous studies that showed that HBZ promotes T-cell growth by enhancing signals through CD3 and that KD of HBZ suppresses the proliferation of ATL cells, including MT-1 cells ( 12 , 48 , 49 ). The alternation of expression of Tax and HBZ seems to execute cooperative programs for survival and proliferation rather than cause them to interfere with each other.…”
Section: Discussionsupporting
confidence: 93%
“…2 B ). This finding is compatible with the previous studies that showed that HBZ promotes T-cell growth by enhancing signals through CD3 and that KD of HBZ suppresses the proliferation of ATL cells, including MT-1 cells ( 12 , 48 , 49 ). The alternation of expression of Tax and HBZ seems to execute cooperative programs for survival and proliferation rather than cause them to interfere with each other.…”
Section: Discussionsupporting
confidence: 93%
“…These observations suggest that coinfection with S. stercoralis or IDH promotes both de novo infection and cell proliferation, which depend on Tax and HBZ, respectively. This idea is compatible with the fact that T‐cell activation enhances the activities of Tax and HBZ on cell proliferation in primary T cells . Thus, inflammation and T‐cell activation caused by the coinfective agent may increase the risk of ATL development in HTLV‐1 positive individuals.…”
Section: Enhancement Of Cancer Development By Coinfection With Multipsupporting
confidence: 57%
“…Anti‐HBZ CTL are less frequent than anti‐Tax CTL in HTLV‐1‐infected subjects despite the constant expression of HBZ, implying that the immunogenicity of HBZ is low . In addition, HBZ suppresses the intracellular inhibitory signal through TIGIT by inactivation of SHP‐2 and, consequently, enhances cell proliferation upon TCR stimulation . Taken together, these reports indicate that Tax stimulates many oncogenic pathways while HBZ counterbalances the negative effects of Tax, leading to malignant transformation of infected cells.…”
Section: Collaboration Of Viral Factors Allows Proliferation Of Infecmentioning
confidence: 93%
See 1 more Smart Citation
“…However, results from another study show that high PD-L1 expression in advanced stages of EBV + ENKTL correlates with improves OS,88 further studies being warranted to establish the prognostic value of PD-L1 expression in these cases. In adult T-cell leukemia/lymphoma (ATLL), HTLV-1 bZIP factor expressed by HTLV-1 infected cells upregulates PD-1 expression on both neoplastic and normal CD4 + T cells, but impedes its suppressive signals by inhibiting co-localization of PD-1 and tyrosine phosphatase (SHP-2), favoring the proliferation of infected cells and immune suppression 89,90. Both asymptomatic HTLV-1 carriers and ATLL patients express high PD-1 levels on HTLV-1-specific cytotoxic T cells, with elevated levels in patients with EBV and CMV co-infection.…”
Section: Introductionmentioning
confidence: 99%